Processos de coagulação e floculação na tratabilidade de água para abastecimento público de Tangará da Serra - MT - Monteiro, Nayra Nalessa de Campos (2020)
Intense and prolonged droughts can cause several important and social impacts, such as the interruption of water supply to the population. With the significant impact on reservoir levels, municipal managers are looking for other alternatives to capture water from a new source of water. Whenever possible, water treatment should be preceded by laboratory tests, in order to technically improve projects and reduce costs. The test in static reactors stands out, which allows the evaluation of the coagulation and flocculation processes and their effects in the following phases of treatment. Thus, the objective of this research was to evaluate the efficiency of the coagulation and flocculation process in the treatment of different raw water for public supply in a medium-sized city in the state of Mato Grosso. Samples were collected in the QueimaPé stream and Sepotuba river during different seasonal periods. The methodology was based on the next steps: preparation of a third sample of water with a mixture of 50% of each spring; characterization of raw waters; tests on static reactors; and cost survey regarding the acquisition of coagulant. The results showed that the exclusion mainly influences the color and turbidity of the waters. Regarding the Sepotuba River, during the drought period, especially in the months of July, August and September, the turbidity of the raw water proved to be inferior and close to the potability standard established by Brazilian legislation. However, it was observed the formation of very fine and small flakes with moderate color removal efficiency and turbidity reaching a maximum value of 44%, which can be justified by the reduced alkalinity of the raw water. Regarding the costs of acquiring coagulant, it was not possible to notice differences between the waters.